PINK1 protects against dendritic cell dysfunction during sepsis through the regulation of mitochondrial quality control - You Wu; Longwang Chen; Zhimin Qiu; Xijing Zhang; Guangju Zhao; Zhongqiu Lu (BMC, 2023)
Abstract Background Dendritic cell (DC) dysfunction plays a central role in sepsis-induced immunosuppression. Recent research has indicated that collective mitochondrial fragmentation contributes to the dysfunction of immune cells observed during sepsis. PTEN-induced putative kinase 1 (PINK1) has been characterized as a guide for impaired mitochondria that can keep mitochondrial homeostasis. However, its role in the function of DCs during sepsis and the related mechanisms remain obscure. In our study, we elucidated the effect of PINK1 on DC function during sepsis and its underlying mechanism of action. Methods Cecal ligation and puncture (CLP) surgery and lipopolysaccharide (LPS) treatment were used as in vivo and in vitro sepsis models, respectively. Results We found that changes in mitochondrial PINK1 expression of DCs paralleled changes in DC function during sepsis. The ratio of DCs expressing MHC-II, CD86, and CD80, the mRNAs level of dendritic cells expressing TNF-α and IL-12, and the level of DC-mediated T-cell proliferation were all decreased, both in vivo and in vitro during sepsis, when PINK1 was knocked out. This suggested that PINK1 knockout prevented the function of DCs during sepsis. Furthermore, PINK1 knockout inhibited Parkin RBR E3 ubiquitin protein (Parkin)-dependent mitophagy and enhanced dynamin-related protein 1 (Drp1)-related mitochondrial fission, and the negative effects of PINK1 knockout on DC function following LPS treatment were reversed by Parkin activation and Drp1 inhibitor. Knockout of PINK1 also increased apoptosis of DCs and the mortality of CLP mice. Conclusion Our results indicated that PINK1 protected against DC dysfunction during sepsis through the regulation of mitochondrial quality control.